Pengaruh Calon Kepala Daerah Perempuan dalam Pilkada: Studi Pilkada Lampung 2015-2018 - M. Iwan Satriawan (Badan Pengawas Pemilihan Umum, 2018)
The aims of this article is to examine the phenomenon of many female regional head as the result of the 2015-2018 election in Lampung Province.Starting from the 2015 election where one regional head and one vice regional head appeared. Then continued in 2017 and 2018, two regional heads and one vice regional head appeared. The method of this research is descriptive qualitative using secondary data from literature studies. The result obtained are the influence of the presence of women candidates in winning regional head elections in Lampung both for regents and governors. Whereas the customs of Lampung society are known as patriarchal where they hold firmly to the existence of men as the main ones in the family, especially in terms of in heritance, customary obligation etc. In contrast with the province of west Sumatera which has matrilineal culture. It means women are the main ones both in the heritance system, customs and others. However, starting from the first regional head election in 2005 to simultaneous local elections in 2018, none has resulted female regional head or their representatives at the district or provincial level. This phenomenon shows the absence of indigenous influences in the head elections, especially in Lampung Province.